The Effect of Compatibilizer on the Mechanical Properties and Compression Set of NBR/EPDM Composite - hesty eka mayasari; agung yanuar wirapraja (Balai Riset Dan Standardisasi Industri Surabaya, 2020)
The mechanical properties of the materials are important to be studied to get the usage information of the material. The NBR/EPDM (Nitrile Butadiene Rubber/Ethylene Propylene Diene Rubber) composite is widely used as seal, gasket, and hose because of their excellent properties. This research used compatibilizer in the blending process of NBR/EPDM. This research aimed to study the effect of some compatibilizer on the mechanical properties and compression set of the NBR/EPDM composite. The compatibilizers used in this research were methyl-methacrylate-butadiene-styrene (MBS), montmorillonite (MMT), and silica. The hardness, tensile strength, elongation at break, tear strength, and compression set of the composites were studied using hardness tester, tensile strength tester, and compression set tester. The research showed that montmorillonite as compatibilizer gave the best hardness, tensile strength, tear strength, elongation, and compression set. The aging increased the hardness and the compression set of NBR/EPDM. However, the aging decreased the tensile strength, tear strength, and elongation at break of NBR/EPDM. Montmorillonite was a suitable compatibilizer for improving the mechanical properties and compression set of NBR/EPDM composite